The Availability of loss of bargain damages upon termination of commercial property leases: Are New Zealand courts perpetuating an unprincipled remedial regime? - Best, Richard (Victoria University of Wellington Law Review, 1994)
In the decision of Morris v Robert Jones Investments Ltd [1994] 2 NZLR 275, the New Zealand Court of Appeal followed the dominant Commonwealth position concerning the availability of loss of bargain damages upon cancellation of contracts of hire and lease. Focussing on commercial property leases, the author argues that this position lacks a sound foundation, and that rather than perpetuate an unprincipled remedial regime the courts should return to first principles of the law of contract.